Four Golden Ages: Regional Interdependency in the Low Countries - Wim Blockmans (BMGN: Low Countries Historical Review, 2012)
Although the Low Countries formed a political unity only for short periods they have been seen by other European nations as a region in its own right. What created some kind of unity, as experienced by the inhabitants? My concept started from the geographical conditions of a delta of three major rivers, in a generally flat area facilitating transport. This was a basic condition for urban growth.